FOOD AND FEEDING OF THE MUD CRAB SCYLLA SERRATA FORSKAL (DECAPODA : PORTUNIDAE) FROM KARWAR WATERS - Prasad, P N; Neelakantan, B (Indian Journal of Fisheries, 2011)
The food habits of the mud crab, Scylla serrata from Karwar waters were studied. A total of 151crabs over a range of 41.04-136.82 mm (carapace width) representing ten size groups were examined. Theprincipal dietary constituents, based on occurrence were crustaceans, detritus, molluscs, fish and miscellaneousitems. Based on volumetric measurements - detritus, fish and crustaceans were the majortrophic components comprising 35.70%, 23.57% and 18.37% of the total food volume respectively.Detritus was the major food group in juvenile crabs (